2017
DOI: 10.1515/ethemes-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Current Account Deficits in the EU Candidate and Potential Candidate Countries: A Panel Analysis

Abstract: This paper presents an empirical investigation of a large number of potentially significant determinants of current account deficits in five EU candidate and potential candidate countries (Albania, Croatia, Macedonia, Serbia and Turkey) in the period 2005 Q1-2015 Q4. Using panel regression techniques we find that current account imbalances in the EU candidate and potential candidate countries are mainly determined by real GDP growth rate and the degree of trade integration. Other factors that have a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…2017;Bošnjak, 2019). This is also the case with the RS (Table 1), where the level and dynamics of the CAD is primarily determined by the negative balance of goods (Boljanović 2012;Bucevska, 2017, Kovačević 2018. The BoP imbalance is further deepened by the primary income deficit as a result of higher expenditures (outflows) than income from investments.…”
Section: The Role Of Surplus Componentsmentioning
confidence: 90%
“…2017;Bošnjak, 2019). This is also the case with the RS (Table 1), where the level and dynamics of the CAD is primarily determined by the negative balance of goods (Boljanović 2012;Bucevska, 2017, Kovačević 2018. The BoP imbalance is further deepened by the primary income deficit as a result of higher expenditures (outflows) than income from investments.…”
Section: The Role Of Surplus Componentsmentioning
confidence: 90%
“…According to [27], trade openness significantly affects the CA balance. furthermore, [23], [37] found that trade openness has a significant positive impact on the CA balance.…”
Section: Datamentioning
confidence: 91%
“…Denisia (2010) points out that benefits of FDI inflows in less developed countries are alternative source of financing substituting the country indebtedness, greater inflow of foreign currency, access to international markets and exports rise. Bucevska (2017) showed that FDI have positive impact on the current account in the candidate countries and potential candidate countries for EU submission, but significant only in the two panel estimation models (Albania, Croatia, North Macedonia, Serbia and Turkey) in the time period (Q12005-Q42015). The author concludes that FDI contribute to the growth of available capital stock and rise in exports industries along with the low contribution in domestic manufacturing and service industry.…”
Section: Literature Reviewmentioning
confidence: 96%